Dissemination and Implementation Research Funded by the US National Institutes of Health, 2005-2012 - Mindy Tinkle; Richard Kimball; Emily A. Haozous; George Shuster; Robin Meize-Grochowski (Hindawi Limited, 2013)
Dissemination and implementation (D&I) research is a growing area of science focused on overcoming the science-practice gap by targeting the distribution of information and adoption of interventions to public health and clinical practice settings. This study examined D&I research projects funded under specific program announcements by the US National Institutes of Health (NIH) from 2005 to 2012. The authors described the projects' D&I strategies, funding by NIH Institute, focus, characteristics of the principal investigators (PIs) and their organizations, and other aspects of study design and setting. Results showed 46 R01s, 6 R03s, and 24 R21s funded totaling $79.2 million. The top funders were the National Cancer Institute and the National Institute of Mental Health, together providing 61% of funding. The majority of PIs were affiliated with Schools of Medicine or large, nonprofit research organizations and think tanks. Only 4% of projects were to PIs with appointments at Schools of Nursing, with 7% of the funding. The most commonly funded projects across all of the studies focused on cancer control and screening, substance abuse prevention and treatment, and mental health services. Typically implemented in community and organizational settings, D&I research provides an excellent opportunity for team science, including nurse scientists and interdisciplinary collaborators.